CONSTRUCTION, EXPRESSION AND PURIFICATION OF RECOMBINANT PRE-MATURE PEPTIDE OF PLANTARICIN F FROM Lactobacillus plantarum S34 IN Escherichia coli - Kusdianawati Kusdianawati; Apon Zaenal Mustopa; Suharsono Suharsono; Bugi Ratno Budiarto; Fatimah Fatimah; Hasim Danuri (Indonesian Journal of Agricultural Science, 2015)
Plantaricin is one of bacteriocins that have the potential to be used as food preservative. Plantaricin is safe for human consumption because it can be easily degraded by proteolytic enzymes. The objective of this study was to express and purify recombinant pre-mature peptide of plantaricin F from Lactobacillus plantarum S34 in Escherichia coli. Plantaricin gene-specific primer was used to obtain pln F structural gene amplicon from L. plantarum S34. This amplicon was cloned in pET32a vector and expressed in E. coli BL21 (DE3) pLysS. Pre-mature plantaricin F peptide was expressed as Histagged-fusion protein and separated by Co2+-chelating affinity chromatography. L. plantarum S34-derived pre-mature plantaricin F peptide fused with thioredoxin-(His)6tag had successfully been expressed in E. coli BL21 (DE3) pLysS using pET32a as an expression vector. The fused recombinant pln F as pre-mature state expressed had a molecular mass of +24 kDa, meanwhile the fused recombinant that contained only the leader peptide of pln F appeared as +20 kDa based on SDS-PAGE separations. The optimal production of fused recombinant pln F as soluble fraction was obtained when culture condition was added with 0.5 mM of IPTG and incubated at 22°C for 5 hours (OD~1). Furthermore, the expression of fused recombinant pln F as its pre-mature peptide pointed out that the pln F’s leader peptide could be proteolytically cleaved by a system in heterologous cells. Overall, heterologous pln F production as pre-mature peptide fused with thioredoxin-(His)6tag had been well established. From this research, we expect plantaricin F can be expressed and purified in E. coli.